Factors that influence the clinical utilization of the nursing process at a hospital in Accra, Ghana - Joana Agyeman-Yeboah; Kwadwo Ameyaw Korsah; Jane Okrah (BMC, 2017)
Abstract Background The nursing process is a tool that is recommended for use by all professional nurses working in Ghana, in order to provide nursing care. However, there is currently a limited use of this tool by nurses in Ghana. The purpose of this research study was to explore the various factors that influence the utilization of this nursing process. Method An exploratory descriptive qualitative-research design was employed. Ten participants were involved by using the purposive sampling method. A semi-structured interview guide was used to collect the data from the research participants; and the data were analysed by using content analysis. One main theme, with five subthemes, emerged from the analysis. Results It was found that there are factors, such as nurses not having a better understanding of the nursing process, whilst in school; the absence of the care plan in the ward, as well as the lack of adequate staff, with limited time being available for coping with contributed to the non-usage of the nursing process. Conclusions We conclude that the clinical utilization of the Nursing process at the clinical setting is influenced by lack of understanding of Nurses on the Nursing process and care plan as well as lack of adequate nurses and time. We recommend that the care-plan form be made officially a part of the admission documents. Furthermore, the nursing administration should put measures in place to provide nurses with the needed resources to implement the nursing process. Additionally, they should ensure that the care-plan forms and other resources needed by the nurses are regularly and adequately provided. Nurses should further see the nursing process as a means of providing comprehensive care to their patients and addressing their specific problems. They should therefore make time despite their busy schedules to use it in order to improve quality of care and the image of nursing in Ghana.